Trial of life: Well infants presenting more than 24 h after head injury with a scalp haematoma: A 10‐year review. (10th May 2018) - Parameswaran, Ahilan; Heitner, Shmuel; Thosar, Deepali; Fowler, Adam; Marks, Susan; O'Leary, Fenton
Abstract : Aim: To review the investigation, patterns of injury and short‐term outcomes of infants younger than 12 months of age who presented more than 24 h after head injury with an isolated scalp haematoma. Methods: A retrospective chart review of infants who presented with a head injury to the emergency department of a major paediatric hospital between 2006 and 2016. Patients were included if they presented more than 24 h after the injury, were clinically well and had a documented scalp haematoma. Charts were abstracted using a standardised instrument to yield patient characteristics, mechanism of injury, imaging performed, identified injuries and patient outcome. Results: A total of 2433 records were reviewed, with 157 included in the study. The mean age was 7.5 months (standard deviation 2.6). Of the patients, 14 had a documented palpable skull fracture; 43 patients had a skull X‐ray reported as a fracture; 13 patients had cranial ultrasounds with 3 reported as having a fracture; 124 patients had computed tomography head imaging, with 112 demonstrating a fracture; and 52 patients had acute intracranial abnormalities. There were nine unplanned representations (5.7%). No patients required any neurosurgical intervention. Conclusions: Infants presenting after 24 h with isolated scalp haematomas had good short‐term outcomes despite a high prevalence of underlying injury on imaging. Expectant management, rather than imaging, may be a valid approach in this patient population. However, some of these injuries may have been the result of inflicted injury, and all of these patients require a robust assessment regardless of the decision to use a computed tomography scan.